FSH Promotes Progesterone Synthesis by Enhancing Autophagy to Accelerate Lipid Droplet Degradation in Porcine Granulosa Cells - Liu, Qiang; Gao, Hui; Yang, Feng; Zhang, Hanxue; Zeng, Shenming (Frontiers in Cell and Developmental Biology, 2021)
Little is known about the molecular relationships among FSH, lipid droplet (LD) degradation, and autophagy. In this study, we aimed to investigate the pathway by which FSH regulates autophagy and the potential role of autophagy in progesterone production. Our results revealed that follicle stimulating hormone (FSH) stimulated progesterone production in mammalian follicular granulosa cells (GCs) through a non-canonical pathway. In porcine secondary follicles cultured in vitro, FSH treatment increased the level of the autophagic marker, LC3-II, as well as increased the number of autophagic vacuoles in GCs. The underlying molecular mechanism and biological functions were then investigated in porcine GCs. Our results demonstrated that FSH could upregulate Beclin1 levels in porcine GCs; however, this effect was blocked by LY294002 (a PI3K/AKT inhibitor) and SP600125 (SAPK/JNK inhibitor). Further research confirmed that the transcriptional factor, c-Jun, was phosphorylated by FSH, then translocated into the nucleus from the cytoplasm and bound to the BECLIN1 promoter region, and that LY294002, SP600125, or c-Jun knockdown prevented the increase in Beclin1 levels induced by FSH. Interestingly, inhibition of autophagy using chloroquine or SP600125 decreased progesterone production in porcine GCs treated with FSH, although the expression of StAR and P450scc was not disturbed. Moreover, FSH treatment reduced the average number and size of LDs in porcine GCs, but these effects were eliminated by knocking down the key autophagy genes, ATG5 and BECLIN1. The effect of FSH on promoting progesterone secretion by the cells was also reduced significantly. Based on the above results, we concluded that FSH promoted progesterone production by enhancing autophagy through upregulation of Beclin1 via the PI3K/JNK/c-Jun pathway to accelerate LD degradation in porcine GCs, independent of the classical steroidogenic pathway.